Identification of transformation products to characterize the ability of a natural wetland to degrade synthetic organic pollutants. (15th December 2020) - Kang, Daeho; Doudrick, Kyle; Park, Naree; Choi, Younghun; Kim, Kyunghyun; Jeon, Junho
Highlights: The natural wetland is polluted by more than 30 synthetic organic substances. Fungicides are dominant pollutants, followed by insecticide and herbicides. Suspect and non-target screening revealed 48 TPs of pesticides in the wetland. QSAR estimations indicate that most TPs are less risky than their parents. The natural wetland is capable of mitigating the risk of pollutants by forming various TPs. Abstract: Natural wetlands have been recognized as a natural reactor for degradation and elimination of environmental pollutants. The Upo Wetland, the largest inland wetland in Korea, is mainly surrounded by agricultural lands and it is susceptible to contamination from excess nutrient loads and synthetic organic contaminants (SOCs) (e.g., pesticides). The aim of this study was to identify major SOCs in the wetland and evaluate their degradation. We used high resolution mass spectrometry (HRMS) with a two-step analysis approach (i.e., 1 st analysis for target measurement along with suspect and non-target screening (SNTS) and 2 nd analysis for complimentary suspect screening) to identify and quantify the transformation products (TPs) of the identified parent SOCs. Quantitative analysis of 30 targets, mainly including pesticides, showed that fungicides were the major SOCs detected in the wetland, accounting for about 50% of the composition ratio of the total SOCs quantified. Orysastrobin occurred at the highest mean concentration (>700 ng/L), followed by two other fungicides, carbendazim and tricyclazole. The first analysis (SNTS) tentatively identified 39 TPs (30 by suspect, 9 by non-target screening) of 14 parent pesticides. Additionally, the second analysis (complimentary suspect screening) identified 9 more TPs. Among the 48 total TPs identified, 7 were confirmed with reference standards. The identification of the remaining TPs had a high confidence level (e.g., level 2 or 3). Regarding transport though the wetland, most TPs showed greater peak area ratios (i.e., the relative portion of chromatographic area of the TPs to the parent compound) at the outlet point of the wetland compared to the inlet point. The risk quotient, which was calculated using the concentrations of parent compounds, decreased toward the outlet, demonstrating the degradation capacity of the wetland. The estimates for biodegradability, hydrophobicity, and toxicity by an in-silico quantitative structure-activity relationship (QSAR) model indicated a lower half-life, lower logDOW, and greater effect concentration for most TPs compared to the parent compounds. Based on these results, we conclude that natural wetlands play a role as an eco-friendly reactor for degrading SOCs to form numerous TPs that are lower risk than the parent compounds. Graphical abstract: Image, graphical abstract